Indikator Kinerja Kunci Gelandang Tengah: Analisis Komparatif Juara Liga 4 Indonesia Level Regional - Habil Muhbaedillah; Dede Rohmat Nurjaya; Berliana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
In the development of modern football, the central midfielder holds a strategic role in maintaining the balance between defensive and offensive phases. This position demands high tactical ability, including decision-making accuracy, ball distribution precision, and effectiveness in winning duels. At the semi-professional level such as Indonesia's Liga 4, the performance of central midfielders across teams still shows variation that can affect overall team effectiveness. This highlights the need for deeper research to understand tactical performance differences and their implications for team strategy. This study was conducted to fill the gap in research on tactical performance differences among central midfielders of regional champion teams. The aim of the study was to analyze the differences in tactical performance of central midfielders between two Liga 4 Indonesia champion teams, namely Cimahi Putra (West Java) and Persebi Boyolali (Central Java). The analysis focused on five Key Performance Indicators: passing accuracy, dribbling success, interceptions, defensive duels won, and crossing accuracy. The study used a comparative descriptive quantitative design through notational analysis of three central midfielders from each team across seven official matches, with data obtained using InStat and LongoMatch software. An independent t-test (p < 0.05) was used to compare the two teams. The results showed two significant differences: Persebi Boyolali outperformed in passing accuracy (88.5% vs. 84.2%), while Cimahi Putra had a higher interception rate (5.8 vs. 4.1). These findings confirm PB's dominance in ball distribution and CP's advantage in ball recovery. Practically, CP needs to improve passing quality after transitions, while PB is advised to strengthen its interception ability. These findings provide an important basis for data-driven strategy development and talent scouting at the regional level. Keywords: Notational Analysis, Central Midfielder, Key Performance Indicators, Tactical Skills, Indonesian Football